Analisis Inversi AIGI Untuk Identifikasi Potensi Hidrokarbon Pada Reservoar Batupasir, Formasi Balikpapan, Lapangan Mustika, Cekungan Kutai, Kalimantan Timur - , ASRIM ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Mustika Field is an oil and gas field that located in south of Kutai Basin, Eas Kalimantan. Field development should be taken to get the maximum production by finding new hydrocarbon potential, which is the target area is flank of anticline in Mustika Field. The field development will be done by delineating sand reservoir and analyzing whatâs the hydrocarbon trap type if any some hydrocarbon potential in the target area. Method that will be used is AIGI inversion. Result of AIGI crossplot with rotation angle 150 to AI axis in E3140 sand reservoir showing any separation between hydrocarbon sand and other litologi and fluid. This means the AIGI inversion can be applied to the target area. Therefore thuning thickness in this reservoir about 32.1 ft and 33.2 ft, which is these thickness allow the minimum thickness to be detected by seismic because E3140 reservoir thickness is 70 ft. AIGI inversion result that have been done showing low AI dan low GI that interpreted as hydrocarbon potential in flank anticlinal at sout east Mustika Field. The wells correlation on the area near from B6 well to the inversion area that having probability for hydrocarbon potential have interpreted as distributary channel. Seismic section along hydrocarbon probability area showing fault as hydrocarbon trap. The combination analysis of inversion result, well correlation and seismic section along hydrocarbon sand area potential showing hydcrocarbon trap in the flank anticlinal of Mustika Field is structural trap.